Learning that makes a difference: Pedagogy and practice for learning abroad - Benham Rennick, Joanne (Teaching and Learning Inquiry, 2015)
As we step into the 21st century human society faces significant new challenges surrounding issues in human health; global security; environmental devastation; human rights violations; economic uncertainty; population explosion and regression; recognition of diversity, difference and special populations at home and abroad. In light of these challenges, there is a great opportunity, and a great need, for education that makes a difference in the way that students think and interact with their world. This article has three objectives. The first is to present an overview of the literature on the global trend to internationalize the higher education curriculum. The second is to briefly highlight some of the key pedagogical concepts established in the work of pedagogical trailblazers John Dewey, Paulo Freire and Jack Mezirow and synthesize them in relation to learning abroad. Finally, the article concludes with a discussion of how a synthesis of these pedagogical models, applied to the context of international learning experiences, has the potential to support transformative learning that makes a difference in how students think about and engage with complex global issues.